Modern technologies and strategies used in smart furniture design. (Al-Academy, 2026)
This study dealt with the topic of (modern technologies and their strategies used in smart furniture design). The first chapter included the research problem, which focused on the following question: - What is the impact of modern technologies on smart furniture design? The importance of this research is to activate the role of modern technologies in providing industrial products with a distinctive design character. The aim of this study is to identify modern technologies and their reflections on smart furniture design. The second chapter contained (the concept of technology and its types used in smart furniture design), while the third chapter included the research methodology, as the research adopted the descriptive approach in analyzing the research sample, and defining the community as a group of global companies for the year (2020), while the fourth chapter included the results and conclusions, the most important of which is that technical development added the possibility of employing different systems within a single product and enhanced aesthetic values through the level of surface output, that the designs were based effectively on technical development and highlighting it as a design achievement in functional performance and containing formal features and characteristics in the form of furniture